2018
DOI: 10.1016/j.forpol.2017.10.003
|View full text |Cite
|
Sign up to set email alerts
|

A Land Use and Resource Allocation (LURA) modeling system for projecting localized forest CO 2 effects of alternative macroeconomic futures

Abstract: The United States has recently set ambitious national goals for greenhouse gas (GHG) reductions over the coming decades. A portion of these reductions are based on expected sequestration and storage contributions from land use, land use change, and forestry (LULUCF). Significant uncertainty exists in future forest markets and thus the potential LULUCF contribution to US GHG reduction goals. This study seeks to inform the discussion by modeling US forest GHG accounts per different simulated demand scenarios acr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
48
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 31 publications
(50 citation statements)
references
References 16 publications
1
48
0
1
Order By: Relevance
“…Previous research has utilized global IPCC scenarios to inform global forest market projections modeling (Buongiorno et al, 2011;Raunikar et al, 2010), and results from the global analyses were then used to simulate U.S. forest harvests and product supply across alternative policy scenarios (Nepal et al, 2012). More recent research uses U.S. focused projections of macroeconomic growth, housing starts, and woody biomass demand to project localized CO 2 emissions associated with forest growth and harvests (Latta et al, 2018). However, these studies lack the level of detail presented in our FSPs, especially in terms of how income growth and SSP policy assumptions can influence technological change and forest management changes at the intensive and extensive margins.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous research has utilized global IPCC scenarios to inform global forest market projections modeling (Buongiorno et al, 2011;Raunikar et al, 2010), and results from the global analyses were then used to simulate U.S. forest harvests and product supply across alternative policy scenarios (Nepal et al, 2012). More recent research uses U.S. focused projections of macroeconomic growth, housing starts, and woody biomass demand to project localized CO 2 emissions associated with forest growth and harvests (Latta et al, 2018). However, these studies lack the level of detail presented in our FSPs, especially in terms of how income growth and SSP policy assumptions can influence technological change and forest management changes at the intensive and extensive margins.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, there is uncertainty in how the demand for forest products will evolve in the future, which may lead to different harvest patterns and land use dynamics over time (Popp et al, 2017). Undoubtedly, societal factors like population, income, and trade, will influence the carbon sequestration potential of the forest sector, and there is a growing literature that seeks to understand how market and policy forces may drive forest carbon trajectories, even at local scales (e.g., Latta et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…For example, a more recent study by Wear and Coulston (2015) showed a decline in annual net sequestration in the U.S. by approximately 45% over the next 25 years. This includes some regions (such as the Southeastern U.S.) that transition from the net sink to the source status (Latta et al 2018). Intensifying biomass removal from forests reduces forest carbon stocks and carbon sink capacity, and thus, may partly offset the climate benefits of forest bioenergy (Haberl et al 2012;Holtsmark 2012a;Repo et al 2011Repo et al , 2012Schlamadinger et al 1995;Schulze et al 2012;Walker et al 2010;Zanchi et al 2011).…”
Section: The Tree Standmentioning
confidence: 99%
“…Forest Service Forest Inventory and Analysis (FIA) plots represent biomass source nodes (United States Forest Service, 2016). The Land Use Resource Allocation (LURA) bioeconomic model determines the projected 20-year average annual forest residue volume available at each FIA plot based on future timber market influences (Martinkus et al, 2017a;Latta et al, 2018). Similar to Chung and Anderson (2012), each FIA point is assumed to be a forest landing and is projected onto the nearest road for use in the TTCM.…”
Section: Total Transportation Cost Model Ttcmmentioning
confidence: 99%